Issues Concerning the Improving Organizational and Legal Support of Victimological Prevention for Environmental Crimes - MALIKOV, Dauren; SIDOROVA, Natalya; ATAKHANOVA, Saltanat; RAKHIMGULOVA, Manshuk; MALIKOVA, Sholpan; KUSSAINOVA, Larissa (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).15, 2023)
Environmental crimes have become a pressing issue in today's world, with the degradation of ecosystems, pollution, and climate change threatening the very foundation of our planet. These crimes not only harm the environment but also have adverse effects on individuals and communities. Recognizing the need for effective prevention strategies, victimological approaches have gained prominence. Victimology focuses on understanding and addressing the needs of the victims, aiming to prevent victimization and promote justice. This essay explores the importance of legal support in victimological prevention of environmental crimes and highlights the key measures required to achieve this goal.